If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4c + 6 = 9(3c + -5) Reorder the terms: 6 + 4c = 9(3c + -5) Reorder the terms: 6 + 4c = 9(-5 + 3c) 6 + 4c = (-5 * 9 + 3c * 9) 6 + 4c = (-45 + 27c) Solving 6 + 4c = -45 + 27c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-27c' to each side of the equation. 6 + 4c + -27c = -45 + 27c + -27c Combine like terms: 4c + -27c = -23c 6 + -23c = -45 + 27c + -27c Combine like terms: 27c + -27c = 0 6 + -23c = -45 + 0 6 + -23c = -45 Add '-6' to each side of the equation. 6 + -6 + -23c = -45 + -6 Combine like terms: 6 + -6 = 0 0 + -23c = -45 + -6 -23c = -45 + -6 Combine like terms: -45 + -6 = -51 -23c = -51 Divide each side by '-23'. c = 2.217391304 Simplifying c = 2.217391304
| H(t)=40 | | 4(y-1)=28 | | 3(j+7)+8j=153 | | 6(-3-x)-3x=14 | | 15z^2+44z-20=0 | | 24x+8y=480 | | x+5=2(4x-3) | | 3n-(-1/2)=-5/2 | | 0.14y+0.06(y+5000)=1100 | | 4(x+3)=2x-5 | | Solveh(t)=40 | | -3=-5(x+6)-8x | | .7(.08+4x)=3x | | 127=4n-2(7n+12) | | 2x+24y+66=14 | | 9j-12j+6j=-42+6 | | 6=10(x+9)-2x | | 7w-10=3w-5w | | 11i+6=28 | | 6y-2t=84 | | -4x+10+5x=-21+10 | | 5=3(x-3)+1-2x | | 6m+5=7m-1 | | 10(-9r-1)=-2r-10 | | -5x^2+3=14x^2-8x | | 6-6x=9x+10 | | -2(3-6h)= | | 6m+5=7n-1 | | 100+8x=444 | | .06p+.08(1700-p)=75 | | 4y-7y-2=0 | | 7x+12=-114 |